Ekstrakurikuler Penggiat Sejarah di SMA Negeri 11 Banjarmasin - Dewi, Mirnawati; Putro, Herry Porda Nugroho (Prabayaksa: Journal of History Education, 2021)
This study discusses extracurricular activities for history activists at SMA Negeri 11 Banjarmasin. The limited subject matter taught in schools about local history in history subject makes students less aware of and familiar with the history of their own area. This study aims to describe the extracurricular activities of history activists at SMA Negeri 11 Banjarmasin. In this study used qualitative methods, in obtaining informations begins with interviews, observations and documentation which are used as research sources. There are two sources of data used in this study, namely primary data sources for coaches, student members of history activists, and secondary sources in the form data of data from schools. History activists extracurricular activities were formed as a place to channel the tallents of history activitiests whi focus on the introduction and knowledge of the local history of the South Kalimantan region.